Projecting Recent Advancements in Battery Technology to Next‐Generation Electric Vehicles. Issue 8 (30th June 2022) - Kim, Sangwook; Tanim, Tanvir R.; Dufek, Eric J.; Scoffield, Don; Pennington, Timothy D.; Gering, Kevin L.; Colclasure, Andrew M.; Mai, Weijie; Meintz, Andrew; Bennett, Jesse
Abstract : Electric vehicles (EVs) have seen rapid growth in adoption over the last several years. Advancements to increase battery life and performance, policy shifts, and high charging rate are expected to further accelerate the development of next generation of EVs. Battery improvements continue to emerge, enabling increased driving range, total distance driven over the life of vehicles, and ability to charge at high rates. Herein, an analysis framework to provide insights into inclusive design metrics, such as specific energy of batteries, energy consumption of vehicles, and charging power infrastructure development, is developed. Various cell‐level fast charge protocols to realistic battery designs to understand the infrastructure needs associated with achieving range replacement of 32.25 km min −1 (20 mi min −1 ) are also scaled. By calculating scaled power and peak to average power ratio, it is found that there needs to be more distinct alignment between the research efforts focused at the cell level and what is being developed for EV charging infrastructure needs. Finally, impact of high direct current voltage architecture in next‐generation EVs is discussed. The findings in this work provide an insight into recent advancements in battery technology to next‐generation EVs. Abstract : Scaling extreme fast charge protocols to relevant battery pack sizes provides an opportunity to understand how fundamental battery research links with infrastructure needs. Herein, it is shown that while some types of protocols may be advantageous to minimize aging, they are impractical when scaled. This information helps guide charge protocol development to increase charge acceptance and minimize infrastructure impacts.